Efektivitas Pemberian Tolvaptan pada Pasien Gagal Jantung dengan Resistensi Diuretik - Suzette Daniel; Devina Sagitania (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Diuretic resistance is a serious complication in heart failure patients associated with increased morbidity and mortality. Tolvaptan, a vasopressin V2 receptor antagonist, offers an alternative therapeutic mechanism through aquaresis. This study aims to evaluate the effectiveness and safety of tolvaptan in heart failure patients with diuretic resistance. A retrospective cohort study was conducted on 58 hospitalized patients with NYHA III-IV heart failure and diuretic resistance (urine output <1000 mL/day despite furosemide use ≥80 mg/day) who received tolvaptan 7.5-15 mg/day for 7 days. Variables measured included weight change, urine output, serum sodium, and kidney function. The results showed a significant increase in daily urine output from 820±230 mL to 2180±520 mL (p<0.001), along with an average weight loss of 3.4±1.1 kg (p<0.001). Hypernatremia (>145 mEq/L) occurred in 8.6% of patients. In conclusion, tolvaptan is effective in improving diuresis and reducing congestion in heart failure patients with diuretic resistance, although the risk of hypernatremia should be monitored.